Association between microRNA-146a, -499a and -196a-2 SNPs and non-small cell lung cancer: a case–control study involving 2249 subjects - Qiu, Hao; Xie, Zhiqiang; Tang, Weifeng; Liu, Chao; Wang, Yafeng; Gu, Haiyong; Zheng, Qingfeng (Bioscience reports, 2021)
MicroRNA (miR) acts as a negative regulator of gene expression. Many literatures have suggested that miRs may be involved in the process of cell proliferation, inflammation, oxidative stress, energy metabolism and epithelial–mesenchymal transition. Thus, miRs may be implicated in the occurrence of non-small cell lung cancer (NSCLC). In the current investigation, we included 2249 subjects (1193 NSCLC patients and 1056 controls) and designed a study to identify the relationship of miR-146a rs2910164 C/G, -499a rs3746444 A/G and -196a-2 rs11614913 T/C with the risk of NSCLC. The risk factors (e.g., body mass index (BMI), sex, smoking, drinking and age) was used to adjust the odds ratios (ORs) and 95% confidence intervals (CIs). After conducting a power value assessment, we did not confirm that the miR-single nucleotide polymorphisms (SNPs) genotypic distributions were different in NSCLC cases and controls. However, the association of miR-196a-2 rs11614913 with a decreased risk of NSCLC was identified in the female subgroup (adjusted P=0.005, power = 0.809 for TC vs. TT, and adjusted P=0.004, power = 0.849 for CC/TC vs. TT). In addition, gene–gene interaction analysis showed that rs11614913 TC/3746444 AA and rs11614913 CC/rs3746444 AA could also reduce the susceptibility to NSCLC (rs11614913 TC/rs3746444 AA vs. rs11614913 TT/rs3746444 AA, P=0.001, power = 0.912 and rs11614913 CC/rs3746444 AA vs. rs11614913 TT/rs3746444 AA, P=0.003, power = 0.836). In conclusion, in overall comparisons, we did not confirm that the rs2910164, rs3746444, and rs11614913 SNPs genotypic distributions were different in NSCLC cases and controls. However, this case–control study demonstrates that miR-196a-2 rs11614913 may be a protective factor for the development of NSCLC among female patients.